O ensino de ciências no contexto inclusivo: flexibilização curricular e apropriação do conhecimento por estudantes com deficiência intelectual - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
The present study focuses on the teaching and learning process involving a student with intellectual disabilities resulting from hydrocephalus in a school unit in the state of Goiás, in the area of Natural Sciences. As a main objective, the relevance of investigating how curricular flexibilization and appropriation of scientific knowledge is being mediated for students with intellectual disabilities in regular education in the state of Goiás is highlighted. The study is based mainly on the Historical-Cultural theory, which has Vygotsky (1997) as one of the main representatives; in the conception of an open, dynamic, flexible and dialogic curriculum studied by Mantoan (2003) and Paganelli (2017); in official documents, in the perspective of the future curriculum defended by Young (2000) and in official documents from federal and state agencies. In addition to the bibliographic review of 30 recent publications, the theoretical precepts underlying the Historical Cultural Theory elaborated by Vygotsky and their contributions to discussions on the school curriculum from the perspective of inclusive education are analyzed. It is proposed to train science teachers in the light of an inclusive curriculum and through the case study it is possible to see how science teaching is being mediated for students with intellectual disabilities. The methodological approach used is of a qualitative nature, the method, case study (LÜDKE and ANDRÉ, 2007), with the objective of apprehending data on the dynamics of the classroom, through the instruments learned in the interviews, field diary and observations which included the interaction of students with intellectual disabilities and other agents involved in their learning process.
Science teaching in the inclusive context: curricular flexibilization and appropriation of knowledge by students with intellectual disabilities
Keywords: Currículo escolar; Educação inclusiva; Deficiência intelectual; School curriculum; Inclusive education; Intellectual disability; EDUCACAO::ENSINO-APRENDIZAGEM; TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL